The Role of Strategic Management in Improving the Quality of Accounting Information Systems at Insurance Companies in Indonesia - Reskino Reskino (Indonesian Management and Accounting Research, 2021)
This study aims to test the role of strategic management in improving the quality of accounting information system. Subject of this research is an insurance company in Indonesia with the number of samples of 35 insurance companies. Sample is an insurance companies consisting of life insurance companies, general insurance companies and state-owned insurance companies in Indonesia are listed in Financial Services Authority The results of statistical tests show that the influence of strategic management on the quality of accounting information systems is significant. Thus it is concluded that the Strategic Management affect the quality of accounting information systems. Implementation of Strategic management in improving the quality of accounting information systems can be done by adopting changes in policies and rules both coming from internal and external environment. Furthermore, information systems can describe the mission and support the organization's goals to achieve competitive advantage The research of strategic management on accounting information systems in insurance companies has not been much studied and currently still requires in-depth study on the role of strategic management on the quality of accounting information systems. With different times and places make this research different research instruments with indicators that match the phenomenon that occurs today so that it can answer the problems that occur. Key words: Strategic Management, Quality of Accounting Information System, Value Added, Performance of the company